Neuromechanical characterization of brain damage in response to head impact and pathological changes - Zolochevsky, Alexander; Martynenko, Alexander (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Traumatic injuries to the central nervous system (brain and spinal cord) have received special attention because of their devastating socio-economical cost. Functional and morphological damage of brain is the most intricate phenomenon in the body. It is the major cause of disability and death. The paper involves constitutive modeling and computational investigations towards an understanding the mechanical and functional failure of brain due to the traumatic (head impact) and pathological (brain tumor) events within the framework of continuum damage mechanics of brain. Development of brain damage has been analyzed at the organ scale with the whole brain, tissue scale with white and gray tissue, and cellular scale with an individual neuron. The mechanisms of neurodamage growth have been specified in response to head impact and brain tumor. Swelling due to electrical activity of nervous cells under electrophysiological impairments, and elastoplastic deformation and creep under mechanical loading of the brain have been analyzed. The constitutive laws of neuromechanical behavior at large strains have been developed, and tension-compression asymmetry, as well as, initial anisotropy of brain tissue was taken into account. Implementation details of the integrated neuromechanical constitutive model including the Hodgkin-Huxley model for voltage into ABAQUS, ANSYS and in-house developed software have been considered in a form of the computer-based structural modeling tools for analyzing stress distributions over time in healthy and diseased brains, for neurodamage analysis and for lifetime predictions of diseased brains. The outcome of this analysis will be how the neuromechanical simulations applied to the head impact and brain tumor therapies may assist medical specialists with their decisions during planning and application of medical surgeries.